Super-resolution optical microscopy (simulation study) - Ong, Nicholas Shi Hong (2018)
This Final Year Project report will provide insight into the Light microscopy technique on how the light are being affected by the changes within the microscope with simulations between Sphere and Elliptic Microbeads to generate ultra-long Photonic Nanojet with a simple, cost effective and easily implemented via the microscope hence it is able to gain enormous attention for super- resolution imaging. The photonic Nanojet generated by silica glass microbeads can out limit the current diffraction limit. Single silica glass bead provides narrow photonic Nanojet with its short length and short working distance limits its applications to surface imaging. There are many possibilities to increase the length of the photonic Nanojet and its working distance by redesigning the sphere design and tweak with its optical properties. This report also includes a step by step on how to do the analysis for the Photonic Nanojet fluence images collected. The study will provide insights for many biomedical imaging applications to have better resolutions.